Ethical hacking techniques and countermeasures for cybercrime prevention - Conteh, Nabie, 1960- (Advances in information security, privacy, and ethics (AISPE) book series., 2021)
"This edited book serves as a guide for certification training, the study of countermeasures to prevent and stop cybercrimes, cyberterrorism, cybertheft, identity theft and computer related crimes"--